Pembelajaran Terintegrasi Sains Dan Agama Islam Sebagai Upaya Pengembangan Karakter Peduli Lingkungan Pada Anak Sekolah Dasar - Mar'attus Sholihah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2021)
Earth is currently in a condition that is quite severe. Environmental damage triggered primarily by human activity has had an impact that threatens the survival of life on earth. Climate change alters the ecological balance that results in natural disasters, water scarcity, and declining environmental quality. Efforts to improve the environment must be a priority and carried out by as many humans as possible. In fact, environmental awareness in Indonesia is still very low. One simple indicator, Indonesia is the second largest contributor of plastic waste in the world. If not addressed, this environmental damage will be felt by all parties. Efforts to increase environmental awareness need to start, one of them through elementary school bench. In line with the Penguatan Pendidikan Karakter (PPK) program, schools can make the environmentally caring character as target character so that learners become the generation that preserves and conserves the environment. Growing character must begin by providing a good understanding and environmental insight to the child as well as a sense of responsibility for himself, his community, and his God. Science learning and Islamic education is the most prospective entrance that teachers can take to foster environmental awareness.